(untitled) (Journal of history, 2019)
To this day, the Afghan war, which occurred in 1979-1889, was widely discussed by the people. It includes international, political, ideological, socio-economic, military aspects. In addition, the main theme of this article is the withdrawal of 40 armies within 10 years to the territory of Afghanistan. This document details the completion of the Afghan war, which caused many difficulties in the life of the USSR. The absence of a formal international agreement on the withdrawal of the Soviet army from Afghanistan in the 1980s led to a deterioration of the condition and pulled the warrior for several years. Only in 1985, an agreement was reached on the withdrawal of Russian military facilities from Afghanistan, as well as on the withdrawal of soldiers. This article openly emphasizes that the Geneva Agreement, signed in 1989, played an important role in the withdrawal of the Soviet army from Afghanistan.